2012
DOI: 10.3998/ark.5550190.0013.709
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of protonated ferrocene isomers in the gas phase and their study by mass spectrometry

Abstract: Gas phase protonation of ferrocene has been studied experimentally in four different reaction systems, using high energy Collision Induced Decomposition mass spectrometry to follow the progress of reaction at different temperatures and pressures. Experimental evidence is obtained for the existence of three stable isomers as predicted theoretically. The most stable form is shown to be most probably metal-protonated, but the energies of the metal-protonated and agostic forms are within 10 kJ mol -1 of each other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(38 reference statements)
2
1
0
Order By: Relevance
“…However, results similar to our H/D exchange data have also been reported by Karlsson et al, who observed by low-temperature 1 H NMR recordings that [ 2 H 10 ]-ferrocene in superacid undergoes only one primary protonation . Moreover, Mason and Kelly did not detect any intramolecular isomerization in their gas-phase protonation study conducted using high-energy collision-induced dissociation mass spectrometry …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, results similar to our H/D exchange data have also been reported by Karlsson et al, who observed by low-temperature 1 H NMR recordings that [ 2 H 10 ]-ferrocene in superacid undergoes only one primary protonation . Moreover, Mason and Kelly did not detect any intramolecular isomerization in their gas-phase protonation study conducted using high-energy collision-induced dissociation mass spectrometry …”
Section: Resultssupporting
confidence: 93%
“…75 Moreover, Mason and Kelly did not detect any intramolecular isomerization in their gas-phase protonation study conducted using high-energy collision-induced dissociation mass spectrometry. 76 Contrary to the small energy difference predicted by computational results, which slightly favors the agostic structure, our own experimental observations on H/D exchange agree with the suggestion that the incipient proton ensconces itself in a sterically unique position and undergoes only one H/D exchange when exposed to D 2 O vapor (Figure 6D). Since experimental evidence, not computational predictions, should take precedence when postulating mechanistic models, we propose that upon collisional activation, the charge-imparting proton migrates to a cp ring and randomizes with its hydrogen atoms (Scheme 1).…”
Section: ■ Results and Discussionsupporting
confidence: 69%
“…+ and H + [24]. The NH 4 + ions in (NH 4 ) 2 S 2 O 8 would likely attach directly onto the metal atoms and the Cp ligands were tilted and loosely bound with metal atoms as a result of the formation of a metastable intermediate phase, decreasing the stability of the metallocene complex [25]. Then the decomposition of persulfate anion (S 2 O 8 2-) took place by this means, cleaving the O-O bond between the two S atoms as the temperature increases, thus converting to a powerful oxidant known as sulfate-free radicals.…”
Section: Resultsmentioning
confidence: 99%